Lithium nickel oxide granular material, preparation method and use thereof
By adopting Li1+xTM1-xO2 particle materials, combined with specific elements and heat treatment technology, an optimized spherical structure is formed, which solves the problems of poor cycle life and increased resistance of the cathode material of lithium-ion batteries, and achieves higher cycle stability and energy density .
Patent Information
- Application Number
- CN202080039010.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-06-28
- Filing Date
- 2020-06-17
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2040-06-17
AI Technical Summary
The existing lithium-ion battery cathode materials such as LiNiO2 have problems such as poor cycle life, significant deflation and increased internal resistance during the cycle, which affects the life and applicability of the battery.
Particulate material of Li1+xTM1-xO2, wherein x is in the range of -0.02 to +0.05, TM contains at least 93 mol% nickel, and Nb, Ta, Ti, Zr, W or Mo and B, Al, Mg, Ga, etc. are added Elements, form spherical or spherical secondary particle structures through specific heat treatment methods, optimizing the microstructure and chemical composition of the material.
It improves the cycle stability and high energy density of the cathode material of lithium-ion batteries, reduces resistance growth, and significantly improves the cycle performance and life of the battery.
Smart Images

Figure BDA0003374923960000131 
Figure BDA0003374923960000141 
Figure BDA0003374923960000201
Abstract
Description
[0001] The present invention relates to a method having a composition of Li 1+x TM 1-x O2 granular material, wherein
[0002] x is in the range of -0.02 to +0.05,
[0003] TM contains at least 93 mol% nickel and
[0004] (A) at least one element M 1 , where M 1 is selected from Nb, Ta, Ti, Zr, W and Mo,
[0005] (B) at least one element M 2 , where M 2 is selected from B, Al, Mg and Ga,
[0006] The particulate material has an average particle diameter (D50) in the range of 2 to 20 μm.
[0007] Lithium-based transition metal oxides are currently used as electrode active materials for lithium-ion batteries. Intensive research and development work has been conducted over the past few years to improve properties such as charge density, specific energy, but also other properties such as reduced cycle life and capacity loss that may adversely affect the life or applicability of lithium-ion batteries. Additional efforts have been made to improve the preparation methods.
[0008] Many of the electrode active materials currently discussed are of the type of lithium-substituted nickel-cobalt-manganese oxide ("NCM material") or lithium-substituted nickel-cobalt-aluminum oxide ("NCA material").
[0009] In a typical method for preparing cathode materials for lithium-ion batteries, a so-called precursor is first formed by coprecipitating the transition metal with a carbonate, an oxide or preferably with a hydroxide that may or may not be alkaline. The precursor is then mixed with a lithium salt such as, but not limited to, LiOH, Li2O or - in particular - Li2CO3 - and calcined (fired) at high temperature. The lithium salt can be used as a hydrate or in a dehydrated form. The calcination - or firing - which is also often referred to as the precursor heat treatment - is usually carried out at a temperature in the range of 600-1,000°C. During the heat treatment, a solid-state reaction occurs and an electrode active material is formed. In the case where a hydroxide or carbonate is used as a precursor, the solid-state reaction is carried out after the removal of water or carbon dioxide. The heat treatment is carried out in the heating zone of a furnace or kiln.
[0010] In order to improve the capacity of the cathode active material, it has been suggested to select as high a nickel content as possible. However, in materials such as LiNiO2, poor cycle life, significant gassing, and a strong increase in internal resistance during cycling have been observed, which poses a great challenge for commercial applications.
[0011] Thus, a particulate material as defined at the outset has been found, hereinafter also defined as inventive material or material according to the invention.In the following, the inventive material will be described in more detail.
[0012] The material of the present invention has a formula Li 1+x TM 1-x The composition of O2,
[0013] x is in the range of -0.02 to +0.05,
[0014] TM contains at least 93 mol% nickel and
[0015] (A) at least one element M 1 , where M 1 is selected from Nb, Ta, Ti, Zr, W and Mo,
[0016] (B) at least one element M 2 , where M 2 is selected from B, Al, Mg and Ga,
[0017] The particulate material has an average particle diameter (D50) in the range of 2 to 20 μm.
[0018] This corresponds to the formula Li 1+x TM 1-x O2, where TM is (Ni 1-x1-x2 M 1 x1 M 2 x2 ), where x1>0, x2>0 and x1+x2≤0.07.
[0019] The materials of the present invention are described in more detail below.
[0020] In one embodiment of the present invention, the material of the present invention comprises spherical particles, i.e. particles having a spherical shape. Spherical particles shall include not only those that are exactly spherical, but also those particles in which the maximum and minimum diameters of at least 90% (number average) of representative samples differ by no more than 10%.
[0021] The material according to the invention has an average particle diameter (D50) in the range of 2 to 20 μm, preferably in the range of 5 to 16 μm. The average particle diameter can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles usually comprise agglomerates of primary particles, and the above-mentioned particle diameters relate to the secondary particle diameters.
[0022] In one embodiment of the present invention, the inventive material comprises secondary particles which are agglomerates of primary particles. Preferably, the inventive material comprises spherical secondary particles which are agglomerates of primary particles. Even more preferably, the inventive material comprises spherical secondary particles which are agglomerates of spherical primary particles or flakes.
[0023] In one embodiment of the invention, the primary particles of the material of the invention have an average diameter in the range of 1 to 2000 nm, preferably 10 to 1000 nm, particularly preferably 50 to 500 nm. The average primary particle diameter can be measured, for example, by SEM or TEM. SEM is the abbreviation for scanning electron microscope, TEM is the abbreviation for transmission electron microscope, and XRD means X-ray diffraction.
[0024] In one embodiment of the present invention, the specific surface area (BET, hereinafter also referred to as "BET surface") of the material of the present invention is in the range of 0.1 to 2.0 M 2 The BET surface can be determined by nitrogen adsorption after degassing the sample at 200° C. for 30 minutes or more and otherwise in accordance with DIN ISO 9277:2010.
[0025] TM is predominantly nickel, for example at least 93 mol%, preferably at least 95 mol%. An upper limit of 99.5 mol% is preferred.
[0026] Some metals are ubiquitous metals such as sodium, calcium or zinc, but such trace amounts are not considered in the description of the present invention. In this context, trace amounts refer to amounts of 0.05 mol% or less relative to the total metal content TM.
[0027] TM is a metal combination according to the general formula (I):
[0028] (Ni a M 1 b M 2 c ) 1-d M 3 d (I)
[0029] in
[0030] M 3 Selected from Mn and Co,
[0031] a is in the range of 0.95 to 0.995, preferably 0.97 to 0.995, more preferably 0.98 to 0.995,
[0032] b is in the range of 0.002 to 0.04,
[0033] c is in the range of 0.002 to 0.02, and
[0034] d is in the range of 0 to 0.02,
[0035] And a+b+c = 1. In a preferred embodiment, b≤c.
[0036] M 1 is selected from Nb, Ta, Ti, Zr, W and Mo, and M 2 Selected from B, Al, Mg and Ga.
[0037] In one embodiment of the present invention, M 1 is Zr or Ti, and M 2 It's Al.
[0038] In one embodiment of the present invention, M 1 is Ta or Nb, and M 2 It is Al or B.
[0039] In one embodiment of the present invention, M 1 and M 2 is uniformly dispersed in the material of the present invention. This means that M 1 and M 2 Approximately uniformly distributed on the particles of the material of the present invention.
[0040] In one embodiment of the present invention, M 1 and M 2 At least one of the compounds is concentrated in the grain boundaries of the particles of the material of the present invention.
[0041] In a specific embodiment of the invention, the secondary particles of the material of the invention are coated with a metal oxide, preferably a metal oxide which is not used as cathode active material. Examples of suitable metal oxides are LiBO2, B2O3, Al2O3, Y2O3, LiAlO2, TiO2, ZrO2, Li2ZrO3, Nb2O5, LiNbO3, Ta2O5, LiTaO3.
[0042] In one embodiment of the invention, the integrated peak width in the differential capacity plot (dQ) / (dV) between 4.1 and 4.25 V in the second charge cycle at 0.2C rate of the inventive material is at least 25 mV. Such inventive materials are particularly useful because they exhibit excellent cycling stability and reduced resistance growth compared to materials with narrower peak widths.
[0043] The differential capacity diagram is usually calculated by differentiating the capacity Q with respect to the voltage V according to Equation 1:
[0044] (dQ) / (dV)=(Q t –Q t–1 ) / (Vt –V t–1 )(Equation 1)
[0045] Where V t , Q t are the voltage V and capacity Q measured at time t, and V t–1 and Q t–1 are the corresponding voltage and capacity measured at the previous time t-1. At a standard C-rate of 0.1-1C, data points are typically measured every 30 to 60 seconds, or after a predetermined voltage change, such as 5mV. The data points can additionally be interpolated and smoothed by appropriate software to improve the quality of the (dQ) / (dV) plot.
[0046] The integrated peak width in the differential capacity (dQ) / (dV) of the second charge between 4.1V and 4.25V at 0.2C rate is defined by the integral I of the corresponding (dQ) / (dV) graph in the second charge between 4.1V and 4.25V divided by the maximum value m of the corresponding (dQ) / (dV) graph in the second charge between 4.1V and 4.25V, as shown in FIG. 1 and defined as Equation 2.
[0047] 第二电荷 IPW 4.1V–4.25V =I / m (Equation 2)
[0048] The materials according to the invention are particularly suitable as cathode active materials for lithium-ion batteries. They combine good cycle stability with high energy density.
[0049] In one embodiment of the present invention, the inventive cathode active material contains Li2CO3 in the range from 0.001 to 1 wt. %, determined by titration with Li2CO3 and relative to said inventive material.
[0050] Another aspect of the present invention relates to a method for preparing the material of the present invention, hereinafter also referred to as the method of the present invention or the method according to the present invention. The method of the present invention comprises several steps, hereinafter also referred to as step (a), step (b) etc.
[0051] Steps (a) to (e) are characterized as follows:
[0052] (a) providing particulate nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide,
[0053] (b) Use one or two M 1 and M 2 treating the nickel oxide / hydroxide with a solution of a compound,
[0054] (c) optionally, removing the solvent from step (b),
[0055] (d) adding a lithium source,
[0056] (e) heat treating the mixture obtained in step (d).
[0057] Steps (a) to (e) are described in more detail below.
[0058] In step (a), particulate nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide, hereinafter also collectively referred to as nickel oxide / hydroxide, is provided. In the context of the present invention, the term nickel oxyhydroxide is not limited to stoichiometric NiOOH, but refers to any nickel compound having only oxygen ions and hydroxide counterions and a maximum individual content of impurities of 2 wt% metal such as Mn or Mg relative to the total metal content of the nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide. Preferably, the nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide has a maximum total impurity content of 2 wt% relative to the total metal content of the nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide.
[0059] The nickel oxide / hydroxide provided in step (a) has an average particle diameter (D50) in the range of 2 to 20 μm, preferably 4 to 16 μm. The average particle diameter can be determined, for example, by light scattering or laser diffraction or electroacoustic spectroscopy. The particles generally comprise agglomerates of primary particles, and the above-mentioned particle diameters relate to secondary particle diameters.
[0060] The preferred nickel oxide / hydroxide is freshly precipitated nickel hydroxide.
[0061] In one embodiment of the present invention, the nickel oxide / hydroxide provided in step (a) has a residual moisture content in the range of 50 to 1,000 ppm, preferably 100 to 400 ppm. The residual moisture content can be determined by Karl-Fischer titration.
[0062] In step (b), the nickel oxide / hydroxide is reacted with one or two M 1 and M 2 The suitable solvent depends on M 1 and M 2 The type of compound.
[0063] Suitable M 1 The compound is an alkoxide or acetylacetonate of Ti, Zr, W, Ta and Nb, such as ethoxylates of Ti, Zr, Nb, W and Ta, isopropoxylates of Ti and Zr, acetylacetonate of Zr, Mo and or W, mixed acetylacetonate-ethoxylate of Ta. 1 The alkoxides are easily soluble in the corresponding alcohols. 1Examples of water-soluble compounds include, but are not limited to, ammonium metatungstate (hydrate), ammonium orthomolybdate, ammonium heptamolybdate, ammonium dimolybdate, ammonium niobium oxalate, ammonium zirconium (IV) carbonate (as is or hydrated).
[0064] Suitable M 2 The compounds are Al2(SO4)3, KAl(SO4)2 and Al(NO3)3, alkoxides of Al, such as but not limited to Al(C2H5O)3, Al-triisopropoxide, Mg(NO3)2, Mg(SO4)2, MgC2O4, alkoxides of Mg, such as but not limited to Mg(C2H5O)2, NaBO2, H3BO3, B2O3, alkoxides of B, such as but not limited to B-triisopropoxide, Ga(NO3)3, Ga2(SO4)3, alkoxides of Ga, such as but not limited to Ga(CH3O)3, Ga-triisopropoxide or mixed salts of at least two cations, such as aluminum magnesium isopropoxide. A suitable solvent for Al2(SO4)3, KAl(SO4)2, Al(NO3)3, Mg(NO3)2, Mg(SO4)2, MgC2O4, NaBO2, H3BO3, B2O3, Ga(NO3)3 and Ga2(SO4)3 is water. 2 The alkoxides are easily soluble in the corresponding alcohols.
[0065] In one embodiment of the present invention, M 1 and M 2 The counterions are the same or similar, for example, two different alkoxide ions. In this embodiment, the nickel oxide / hydroxide can be prepared with a nickel hydroxide containing M 1 and M 2 Solution treatment.
[0066] In another embodiment of the present invention, M 1 and M 2 The counterions are different, for example, M 1 In this embodiment, the nickel oxide / hydroxide is then reacted with a mixture containing M 1 The solution and the 2 Solution treatment.
[0067] In one embodiment of step (b), the solution used in step (b) contains 0.001-60 wt % of M 1 or M 2 In another embodiment of step (b), the solution used in step (b) contains 0.002-70% by weight of M 1 and M 2 of compounds.
[0068] In one embodiment of the present invention, step (b) is carried out at a temperature in the range of 5-85°C, preferably 10-60°C.
[0069] In one embodiment of the present invention, step (b) is carried out at atmospheric pressure. However, it is preferred that step (b) is carried out at elevated pressure, for example 10 mbar to 10 bar higher than atmospheric pressure, or under suction, for example 50-250 mbar lower than atmospheric pressure, preferably 100-200 mbar lower than atmospheric pressure.
[0070] Step (b) can be carried out, for example, in a container that can be easily discharged, for example due to its location above the filtering device. The nickel oxide / hydroxide of step (a) can be added to the container, and then M 1 and M 2 In another embodiment, M is added to the container. 1 and M 2 In another embodiment, the nickel oxide / hydroxide and M of step (a) are simultaneously introduced. 1 and M 2 A solution of a compound.
[0071] In one embodiment of the present invention, in step (b), the nickel oxide / hydroxide / oxyhydroxide of step (a) and all the M 1 and M 2 The volume ratio of the solution of the compound is in the range of 10:1-1:5, preferably 10:1-1:1, even more preferably 10:1 to 5:1.
[0072] Use M 1 and M 2 The solution treatment of nickel oxide / hydroxide may be carried out for a period of time ranging from 1 minute to 3 hours, preferably from 5 minutes to 1 hour, and even more preferably from 5 to 30 minutes.
[0073] Step (b) may be assisted by a mixing operation, such as shaking or in particular stirring or shearing, see below.
[0074] In one embodiment of the present invention, steps (b) and (c) are combined: In one embodiment of the present invention, step (b) is carried out by mixing the nickel oxide / hydroxide of step (a) in a solution containing M 1 The solvent is then removed by solid-liquid separation or evaporation, step (c-1), and the residue is then slurried in a solution containing M 2 The step (c-2) is carried out by reslurrying the mixture in a solution of , removing the corresponding solvent by a solid-liquid separation method or evaporation, and drying at a maximum temperature in the range of 50 to 450°C.
[0075] In another embodiment of the present invention, step (b) is carried out by mixing the nickel oxide / hydroxide of step (a) in a solution containing M 2 The solvent is then removed by solid-liquid separation or evaporation, step (c-1), and the residue is then slurried in a solution containing M 1 The step (c-2) is carried out by reslurrying the mixture in a solution of , removing the corresponding solvent by a solid-liquid separation method or evaporation, and drying at a maximum temperature in the range of 50 to 450°C.
[0076] In optional step (c), the solvent is removed. Suitable embodiments for removing the solvent are solid-liquid separation methods, such as decantation and filtration, for example on a belt filter or in a filter press.
[0077] In one embodiment of step (c), the slurry obtained in step (b) is discharged directly into a centrifuge, such as a decanter centrifuge or a filter centrifuge, or a filtering device, such as a suction filter or a belt filter, which is preferably located directly below the container in which step (b) is carried out. Filtration is then started.
[0078] In a particularly preferred embodiment of the present invention, steps (b) and (c) are carried out in a filtration apparatus with a stirrer, such as a filter press with a stirrer or a suction filter with a stirrer. 1 and M 2 3 minutes after - or even immediately thereafter - the removal of solvent begins by starting filtration. On a laboratory scale, steps (b) and (c) can be performed on a Buchner funnel and steps (b) and (c) can be assisted by manual stirring.
[0079] In a preferred embodiment, step (b) is carried out in a filtration device, such as a stirred filtration device that allows the slurry or filter cake to be stirred in the filter. Step (c) is started at most 3 minutes after starting step (b) by starting filtration, such as filter pressing or suction filtration.
[0080] In one embodiment of the present invention, the solvent removal according to step (c) has a duration in the range of 1 minute to 1 hour.
[0081] In one embodiment of the present invention, stirring in steps (b) and (c) (if applicable) is carried out at a rate in the range of 1 to 50 revolutions per minute ("rpm"), preferably 5 to 20 rpm.
[0082] In one embodiment of the present invention, the filter medium may be selected from the group consisting of ceramics, sintered glass, sintered metal, organic polymer films, nonwovens and fabrics.
[0083] In one embodiment of the invention, steps (b) and (c) are carried out in an atmosphere with reduced CO2 content and / or water content, for example, a carbon dioxide content and / or water content in the range of 0.01 to 500 ppm by weight, preferably 0.1 to 50 ppm by weight. CO2 content and / or water content can be measured, for example, by an optical method using infrared light. Even more preferably, steps (b) and (c) are carried out in an atmosphere in which the carbon dioxide content and / or water content are below the detection limit of an optical method based on infrared light.
[0084] In one embodiment of the present invention, step (c) is carried out by evaporating the solvent, preferably by evaporating the solvent under reduced pressure. This embodiment is preferred when the solvent is an organic solvent such as ethanol or isopropanol.
[0085] In one embodiment of the present invention, the 1 and M 2 The solvent of the solution treated wet nickel oxide / hydroxide is directly mixed with the lithium source, step (d), to achieve an ideal distribution of lithium. This option is particularly interesting if only water is used as the solvent of step (b).
[0086] In one embodiment of the invention, steps (b) and (c) are carried out in an atmosphere with a reduced CO2 content, for example a carbon dioxide content in the range of 0.01 to 500 ppm by weight, preferably 0.1 to 50 ppm by weight. The CO2 content can be determined, for example, by an optical method using infrared light. Even more preferably, steps (b) and (c) are carried out in an atmosphere in which the carbon dioxide content is below the detection limit of an optical method, for example based on infrared light.
[0087] In one embodiment of the present invention, step (c) is carried out by evaporating the solvent, preferably by evaporating the solvent under reduced pressure. This embodiment is preferred when the solvent is an organic solvent such as ethanol or isopropanol.
[0088] In the embodiment wherein step (c) is performed, a powdery residue is obtained from step (c).
[0089] In step (d), a lithium source is added.
[0090] Examples of lithium sources are Li2O, LiOH and Li2CO3, each free from water or, if applicable, as a hydrate, for example LiOH.H2O. A preferred example is lithium hydroxide.
[0091] The amounts of the lithium source and the powdery residue are selected in such a way that the molar ratio of Li to TM is (1+x):1, wherein x is in the range of 0.98 to 1.05.
[0092] The lithium source is preferably in the form of particles, for example having an average diameter (D50) in the range of 3-10 μm, preferably 5-9 μm.
[0093] Examples of suitable equipment for carrying out step (d) are high shear mixers, tumble mixers, plowshare mixers and free fall mixers.
[0094] In one embodiment of the present invention, step (d) is carried out at a temperature ranging from ambient temperature to 200°C, preferably from 20 to 50°C.
[0095] A mixture was obtained.
[0096] Step (e) comprises subjecting the mixture to a thermal treatment. An example of step (e) is thermal treatment at a temperature in the range of 600 to 800° C., preferably 650 to 750° C. The terms “treating thermally” and “heat treatment” are used interchangeably in the context of the present invention.
[0097] In one embodiment of the present invention, the mixture obtained from step (d) is heated to 600 to 800°C at a heating rate of 0.1 to 10°C / min.
[0098] In one embodiment of the present invention, the temperature is increased before reaching the desired temperature of 600 to 800° C., preferably 650 to 750° C. For example, the mixture obtained from step (d) is first heated to a temperature of 350 to 550° C., then kept constant for a period of 10 minutes to 4 hours, then it is increased to 650 to 800° C., and then kept at 650 to 800° C. for 10 minutes to 10 hours.
[0099] In one embodiment of the invention, step (e) is carried out in a roller hearth kiln, a pusher kiln or a rotary kiln or a combination of at least two of the foregoing. A rotary kiln has the advantage that the material produced therein is very well homogenized. In roller hearth kilns and pusher kilns, different reaction conditions can be set very easily for the different steps. In laboratory-scale experiments, box and tube furnaces as well as split-tube furnaces are also feasible.
[0100] In one embodiment of the invention, step (e) is carried out in an oxygen-containing atmosphere, for example, in a nitrogen-air mixture, a noble gas-oxygen mixture, air, oxygen or oxygen-enriched air. In a preferred embodiment, the atmosphere in step (d) is selected from air, oxygen and oxygen-enriched air. Oxygen-enriched air can be, for example, a 50:50 volume ratio mixture of air and oxygen. Other schemes are a 1:2 volume ratio mixture of air and oxygen, a 1:3 volume ratio mixture of air and oxygen, a 2:1 volume ratio mixture of air and oxygen and a 3:1 volume ratio mixture of air and oxygen.
[0101] In one embodiment of the present invention, step (e) is carried out under a gas stream, such as air, oxygen and oxygen-enriched air. Such gas streams can be referred to as forced gas streams. Such gas streams can have a flow rate of 0.5 to 15 m / s. 3 / h·kg According to the general formula Li 1+x TM 1-x The specific flow rate of O2 in the material range. This amount is determined under normal conditions: 298K and 1 atmosphere. The gas stream can be used to remove gaseous cracking products such as water and carbon dioxide.
[0102] The process of the present invention may include further steps such as, but not limited to, an additional calcination step at a temperature in the range of 650 to 800° C. after step (b).
[0103] In one embodiment of the invention, step (e) has a duration in the range of 1 hour to 30 hours. Preferably 10-24 hours. The time at temperatures above 600°C, heating and holding, is calculated, but cooling time is ignored in this regard.
[0104] The obtained material is very suitable as cathode active material for lithium-ion batteries.
[0105] In one embodiment of the invention, the material of the invention can be treated with water and then dried. In another embodiment, the particles of the material of the invention can be at least partially coated, for example by mixing them with an oxide or hydroxide, for example with aluminum hydroxide or aluminum oxide or with boric acid, and then heat-treating them at 150 to 400° C. In another embodiment of the invention, the particles of the material of the invention can be at least partially coated by an atomic layer deposition method, for example by alternating treatment with trimethylaluminum and water for 8 s.
[0106] Another aspect of the invention is an electrode comprising at least one material according to the invention. They are particularly useful for lithium-ion batteries. Lithium-ion batteries comprising at least one electrode according to the invention exhibit very good discharge and cycling behavior, and they exhibit good safety behavior.
[0107] In one embodiment of the present invention, the cathode of the present invention comprises:
[0108] (A) at least one material according to the invention as described above,
[0109] (B) carbon in a conductive state, and
[0110] (C) an adhesive,
[0111] (D) Current collector.
[0112] In a preferred embodiment of the present invention, the cathode of the present invention comprises
[0113] (A) 80-98% by weight of the material of the present invention,
[0114] (B) 1-17% by weight of carbon,
[0115] (C) 1-10 wt. % of a binder material,
[0116] Percentages are relative to the sum of (A), (B), and (C).
[0117] The electrode according to the invention comprises carbon in a conductive form, referred to as carbon (B). Carbon (B) may be selected from soot, activated carbon, carbon nanotubes, graphene and graphite. Carbon (B) may be added as is during the preparation of the electrode material of the invention.
[0118] The electrodes according to the present invention may contain other components. They may include a current collector (D), such as but not limited to aluminum foil. They further include a binder material (C), hereinafter also referred to as binder (C). The current collector (D) is not further described herein.
[0119] Suitable binders (C) are preferably selected from organic (co)polymers. Suitable (co)polymers, i.e. homopolymers or copolymers, can be selected, for example, from (co)polymers obtainable by anionic, catalytic or free radical (co)polymerization, in particular polyethylene, polyacrylonitrile, polybutadiene, polystyrene and copolymers of at least two comonomers selected from ethylene, propylene, styrene, (meth)acrylonitrile and 1,3-butadiene. Polypropylene is also suitable. Additionally suitable are polyisoprene and polyacrylates. Polyacrylonitrile is particularly preferred.
[0120] In the context of the present invention, polyacrylonitrile is understood to mean not only polyacrylonitrile homopolymers but also copolymers of acrylonitrile with 1,3-butadiene or styrene. Preference is given to polyacrylonitrile homopolymers.
[0121] In the context of the present invention, polyethylene is to be understood not only as meaning homopolyethylene but also as meaning ethylene copolymers which comprise at least 50 mol % of copolymerized ethylene and up to 50 mol % of at least one further comonomer, for example α-olefins such as propylene, butene (1-butene), 1-hexene, 1-octene, 1-decene, 1-dodecene, 1-pentene and also isobutene, vinyl aromatics such as styrene and also (meth)acrylic acid, vinyl acetate, vinyl propionate, C1-C2-6-(meth)acrylic acid. 10 Alkyl esters, in particular methyl acrylate, methyl methacrylate, ethyl acrylate, ethyl methacrylate, n-butyl acrylate, 2-ethylhexyl acrylate, n-butyl methacrylate, 2-ethylhexyl methacrylate, and also maleic acid, maleic anhydride and itaconic anhydride. The polyethylene may be HDPE or LDPE.
[0122] In the context of the present invention, polypropylene is understood not only to mean homopolypropylene, but also to mean propylene copolymers comprising at least 50 mol % copolymerized propylene and up to 50 mol % of at least one other comonomer, such as ethylene and α-olefins such as butene, 1-hexene, 1-octene, 1-decene, 1-dodecene and 1-pentene. The polypropylene is preferably isotactic or substantially isotactic polypropylene.
[0123] In the context of the present invention, polystyrene is understood not only as meaning styrene homopolymers but also as meaning C1-C12-C16-Hydroxy-1,1-diene, (meth)acrylic acid, (meth)acrylic acid and 1,3-butadiene. 10 Copolymers of alkyl esters, divinylbenzene, especially 1,3-divinylbenzene, 1,2-diphenylethylene and α-methylstyrene.
[0124] Another preferred binder (C) is polybutadiene.
[0125] Other suitable binders (C) are selected from the group consisting of polyethylene oxide (PEO), cellulose, carboxymethyl cellulose, polyimide and polyvinyl alcohol.
[0126] In one embodiment of the present invention, the binder (C) is selected from those having an average molecular weight M w (Co)polymers in the range of 50,000-1,000,000 g / mol, preferably 50,000-500,000 g / mol.
[0127] The binder (C) may be a crosslinked or non-crosslinked (co)polymer.
[0128] In a particularly preferred embodiment of the present invention, binder (C) is selected from halogenated (co)polymers, especially fluorinated (co)polymers. Halogenated or fluorinated (co)polymers are understood to refer to (co)polymers comprising at least one (co)polymerized (co)monomer, wherein each molecule of the (co)monomer has at least one halogen atom or at least one fluorine atom, and more preferably each molecule has at least two halogen atoms or at least two fluorine atoms. Examples are polyvinyl chloride, polyvinylidene chloride, polytetrafluoroethylene, polyvinylidene fluoride (PVdF), tetrafluoroethylene-hexafluoropropylene copolymer, vinylidene fluoride-hexafluoropropylene copolymer (PVdF-HFP), vinylidene fluoride-tetrafluoroethylene copolymer, perfluoroalkyl vinyl ether copolymer, ethylene-tetrafluoroethylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer and ethylene-chlorofluoroethylene copolymer.
[0129] Suitable binders (C) are, in particular, polyvinyl alcohols and halogenated (co)polymers, for example polyvinyl chloride or polyvinylidene chloride, and in particular fluorinated (co)polymers, such as polyvinyl fluoride and in particular polyvinylidene fluoride and polytetrafluoroethylene.
[0130] The electrode of the present invention may contain 3 to 10 wt % of the binder (d) relative to the sum of the component (a), the component (b) and the carbon (c).
[0131] Another aspect of the present invention is a battery pack comprising
[0132] (A) at least one cathode comprising the cathode active material (A) of the present invention, carbon (B) and a binder (C),
[0133] (B) at least one anode, and
[0134] (C) at least one electrolyte.
[0135] Embodiments of the cathode (1) have been described in detail above.
[0136] The anode (2) may contain at least one anode active material, such as carbon (graphite), TiO2, titanium lithium oxide, silicon or tin. The anode (2) may additionally contain a current collector, for example a metal foil such as copper foil.
[0137] The electrolyte (3) may contain at least one non-aqueous solvent, at least one electrolyte salt and, optionally, additives.
[0138] The nonaqueous solvent used for the electrolyte (3) may be liquid or solid at room temperature and is preferably selected from polymers, cyclic or acyclic ethers, cyclic and acyclic acetals, and cyclic or acyclic organic carbonates.
[0139] Examples of suitable polymers are in particular polyalkylene glycols, preferably poly-C1-C4 alkylene glycols and in particular polyethylene glycol. The polyethylene glycol here may contain up to 20 mol % of one or more C1-C4 alkylene glycols. The polyalkylene glycol is preferably a polyalkylene glycol with two methyl or ethyl end caps.
[0140] The molecular weight M of suitable polyalkylene glycols and in particular suitable polyethylene glycols is w It may be at least 400 g / mol.
[0141] The molecular weight M of suitable polyalkylene glycols and in particular suitable polyethylene glycols is w It may be at most 5 000 000 g / mol, preferably at most 2 000 000 g / mol.
[0142] Examples of suitable acyclic ethers are, for example, diisopropyl ether, di-n-butyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, of which 1,2-dimethoxyethane is preferred.
[0143] Examples of suitable cyclic ethers are tetrahydrofuran and 1,4-dihydrofuran. alkyl.
[0144] Examples of suitable acyclic acetals are, for example, dimethoxymethane, diethoxymethane, 1,1-dimethoxyethane and 1,1-diethoxyethane.
[0145] Examples of suitable cyclic acetals are 1,3-di- Alkanes and especially 1,3-dioxolane.
[0146] Examples of suitable acyclic organic carbonates are dimethyl carbonate, ethyl methyl carbonate and diethyl carbonate.
[0147] Examples of suitable cyclic organic carbonates are compounds of the general formulae (II) and (III):
[0148]
[0149] Where R 1 , R 2 and R 3 may be the same or different and are selected from hydrogen and C1-C4 alkyl, such as methyl, ethyl, n-propyl, isopropyl, n-butyl, isobutyl, sec-butyl and tert-butyl, wherein R 2 and R 3 Not tert-butyl at the same time.
[0150] In a particularly preferred embodiment, R 1 is methyl and R 2 and R 3 Each is hydrogen, or R 1 , R 2 and R 3 Each is hydrogen.
[0151] Another preferred cyclic organic carbonate is vinylene carbonate of formula (IV):
[0152]
[0153] The solvent or solvents are preferably used in anhydrous state, ie with a water content in the range from 1 ppm to 0.1% by weight, as can be determined, for example, by Karl-Fischer titration.
[0154] The electrolyte (3) further comprises at least one electrolyte salt. Suitable electrolyte salts are in particular lithium salts. Examples of suitable lithium salts are LiPF6, LiBF4, LiClO4, LiAsF6, LiCF3SO3, LiC(C n F 2n+1 SO2)3, lithium imide such as LiN(C n F 2n+1SO2)2, wherein n is an integer in the range of 1-20, LiN(SO2F)2, Li2SiF6, LiSbF6, LiAlCl4 and the general formula (C n F 2n+ 1SO2) t A salt of YLi, wherein m is defined as follows:
[0155] When Y is selected from oxygen and sulfur, t=1,
[0156] When Y is selected from nitrogen and phosphorus, t=2, and
[0157] When Y is selected from carbon and silicon, t=3.
[0158] Preferred electrolyte salts are selected from LiC(CF3SO2)3, LiN(CF3SO2)2, LiPF6, LiBF4, LiClO4, among which LiPF6 and LiN(CF3SO2)2 are particularly preferred.
[0159] In a preferred embodiment of the invention, the electrolyte (3) contains at least one flame retardant. Useful flame retardants can be selected from trialkyl phosphates, the alkyl groups being different or the same, triaryl phosphates, dialkyl phosphonates, and trialkyl phosphonates. Preferred are tri-C1-C4 alkyl phosphates, the C1-C4 alkyl groups being different or the same, tribenzyl phosphate, triphenyl phosphate, di-C1-C4 alkyl phosphonates, and tri-C1-C4 alkyl phosphonates.
[0160] In a preferred embodiment, the electrolyte (3) comprises at least one flame retardant selected from trimethyl phosphate, CH3-P(O)(OCH3)2, triphenyl phosphate and tris-(2,2,2-trifluoroethyl) phosphate.
[0161] The electrolyte (3) may contain 1 to 10 wt % of a flame retardant based on the total amount of the electrolyte.
[0162] In an embodiment of the invention, the battery according to the invention comprises one or more separators (4) by means of which the electrodes are mechanically separated. Suitable separators (4) are polymer films which are not reactive toward metallic lithium, in particular porous polymer films. Particularly suitable materials for separators (4) are polyolefins, in particular porous film-forming polyethylene and porous film-forming polypropylene.
[0163] The separator (4) made of polyolefin, especially polyethylene or polypropylene, may have a porosity in the range of 35-45%. Suitable pore sizes are, for example, in the range of 30-500 nm.
[0164] In another embodiment of the present invention, the separator (4) may be selected from PET nonwovens filled with inorganic particles. Such separators may have a porosity in the range of 40-55%. Suitable pore sizes are, for example, in the range of 80-750 nm.
[0165] The battery pack of the present invention may further include an outer cover which may have any shape, such as a cubic or cylindrical disc shape. In one version, a metal foil configured into a pouch is used as the outer cover.
[0166] The inventive battery provides very good discharge and cycling behavior, especially at high temperatures (45° C. or higher, such as up to 60° C.), especially with regard to capacity loss.
[0167] The battery according to the invention may comprise two or more electrochemical cells combined with one another, which may be connected in series or in parallel, for example. Preferably they are connected in series. In the battery according to the invention, at least one electrochemical cell contains at least one electrode according to the invention. Preferably, in the electrochemical cell according to the invention, the majority of the electrochemical cells contain an electrode according to the invention. Even more preferably, all electrochemical cells in the battery according to the invention contain an electrode according to the invention.
[0168] The invention further provides the use of the battery according to the invention in a device, in particular in a mobile device. Examples of mobile devices are vehicles, such as cars, bicycles, airplanes, or water vehicles such as ships or boats. Other examples of mobile devices are those that are moved manually, such as computers, in particular laptop computers, telephones or electric hand tools, such as electric hand tools in the construction field, in particular drills, battery-powered screwdrivers or battery-powered staplers. BRIEF DESCRIPTION OF THE DRAWINGS
[0170] Figure 1: Integrated peak width of the second charge at 0.2C rate between 4.1V and 4.25V Second charge IPW 4.1V–4.25V Calculation instructions.
[0171] Figure 2: Differential capacity diagram (dQ) / (dV) of the second cycle of a coin-type half-cell containing C-CAM.1 and obtained by applying the cycling program listed in Table 1.
[0172] FIG. 3 : Differential capacity diagram (dQ) / (dV) of the second cycle of a coin-type half-cell containing CAM.2 obtained by applying the cycling program listed in Table 1.
[0173] FIG. 4 : Differential capacity diagram (dQ) / (dV) of the second cycle of a coin-type half-cell containing CAM.3 obtained by applying the cycling program listed in Table 1.
[0174] FIG. 5 : Differential capacity diagram (dQ) / (dV) of the second cycle of a coin-type half-cell containing CAM.4 obtained by applying the cycling program listed in Table 1.
[0175] FIG. 6 : Differential capacity diagram (dQ) / (dV) of the second cycle of a coin-type half-cell containing CAM.5 obtained by applying the cycling program listed in Table 1.
[0176] Figure 7: Capacity cycling diagram of coin-type half-cells containing C-CAM.1 obtained by applying the cycling program listed in Table 1.
[0177] Figure 8: Capacity cycling diagram of coin-type half-cells containing CAM.2 obtained by applying the cycling program listed in Table 1.
[0178] Figure 9: Capacity cycling diagram of a coin-type half-cell containing CAM.3 obtained by applying the cycling program listed in Table 1.
[0179] FIG. 10 : Capacity cycling diagram of a coin-type half-cell containing CAM.4 obtained by applying the cycling program listed in Table 1.
[0180] FIG. 11 : Capacity cycling diagram of a button-type half-cell containing the cathode active material C-CAM.5 according to the invention obtained by applying the cycling program listed in Table 1.
[0181] 12 : Resistance cycling diagrams of button-type half-cells containing comparative cathode active material C-CAM.1 and inventive cathode active materials CAM.2, CAM.3 and CAM.4 obtained by applying the cycling program listed in Table 1.
[0182] The invention is further illustrated by working examples.
[0183] The average particle diameter (D50) is determined by dynamic light scattering ("DLS"). Unless otherwise specifically stated, percentages are by weight.
[0184] Step (a.1): A spherical Ni(OH)2 precursor is obtained by combining an aqueous nickel sulfate solution (1.65 mol / kg solution) with a 25 wt% aqueous NaOH solution and using ammonia as a complexing agent. The pH value is set to 12.6. The freshly precipitated Ni(OH)2 is washed with water, sieved and dried at 120°C for 12 hours. Subsequently, the freshly precipitated Ni(OH)2 is poured into an alumina crucible and dried in an oxygen atmosphere (10 exchanges / h) at 500°C in a furnace at a heating rate of 3°C / min and a cooling rate of 10°C / min for 3 hours to obtain the precursor p-CAM.1. p-CAM.1 is NiO with a D50 of 6μm.
[0185] Preparation of comparative cathode active material C-CAM.1:
[0186] The dehydrated precursor p-CAM.1 was mixed with LiOH·H2O at a molar ratio of Li:Ni of 1.01:1, poured into an alumina crucible, and heated at 350°C for 4 hours and at 700°C for 6 hours using a heating rate of 3°C / min under an oxygen atmosphere (10 exchanges / h). The resulting material was cooled to ambient temperature at a cooling rate of 10°C / min and then sieved with a mesh size of 30 μm to obtain a comparative material C-CAM.1 with a D50 of 6 μm.
[0187] Preparation of the material CAM.2 of the present invention:
[0188] Step (b.1.2): 100 g of the precursor p-CAM.1 is placed in a beaker. 0.98 g of anhydrous Al(NO3)3 and 0.32 g of boric acid H3BO3 are dissolved in 35 ml of deionized water. The resulting solution is added dropwise to the beaker through a dropping funnel over 5 minutes at ambient temperature until the precursor is soaked in the liquid. No visible liquid film is formed on the precursor p-CAM.1. The resulting slurry is stirred in a beaker for 30 minutes. The individual amounts of Al, B and Ni are set to ensure that the molar ratio of Ni:Al is 0.991:0.002 and the molar ratio of Ni:B is 0.991:0.004.
[0189] Step (c.1.2): Subsequently, water was removed by heating the mixture at 120° C. for 6 hours under vacuum to obtain p-CAM.2.1.
[0190] Step (b.2.2): Place p-CAM.2.1 obtained from (c.1.2) in a beaker. Dissolve 1.24 g of niobium (V) ethoxide in 28 ml of anhydrous ethanol. Add the resulting solution dropwise to the beaker through a dropping funnel over 5 minutes at ambient temperature until the precursor is soaked in liquid. No visible liquid film is formed above the precursor p-CAM.2.1. Stir the resulting slurry in the beaker for 30 minutes. Step (b.2.2) is carried out under a nitrogen environment. The individual amounts of Nb and Ni are set to ensure that the molar ratio of Ni:Nb is 0.991:0.003.
[0191] Step (c.2.2): Subsequently, the ethanol was removed by heating the slurry at 120° C. for 6 hours under vacuum to obtain p-CAM.2.2.
[0192] Steps (d.1.2) and (e.1.2): The precursor p-CAM.2.2 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Nb+B+Al) of 1.01:1, poured into an alumina crucible, and heated at 350°C for 4 hours and at 700°C for 6 hours under an oxygen atmosphere (10 exchanges / h) at a heating rate of 3°C / min and a cooling rate of 10°C / min. The material thus obtained was subsequently sieved with a mesh size of 30 μm to obtain the cathode active material CAM.2 of the present invention.
[0193] D50: 6μm.
[0194] Preparation of the material CAM.3 of the present invention:
[0195] Step (b.1.3): Place 100 g of the precursor p-CAM.1 in a beaker. Add 1.80 g of Ga(NO3)3 nitrate and 0.52 g of ammonium heptamolybdate (NH4)6Mo7O 24 Dissolve in 35 ml of deionized water. Add the resulting solution dropwise into a beaker at ambient temperature through a dropping funnel over 5 minutes until the precursor is soaked with liquid. No visible liquid film is formed above the precursor p-CAM.1. Stir the resulting slurry in a beaker for 30 minutes. Set the individual amounts of Ga, Mo and Ni to ensure that the molar ratio of Ni:Mo is 0.991:0.002 and the molar ratio of Ni:Ga is 0.991:0.004.
[0196] Step (c.1.3): Subsequently, water was removed by heating the slurry at 120° C. for 6 hours under vacuum to obtain p-CAM.3.1.
[0197] Step (b.2.3): Place p-CAM.3.1 obtained from (c.1.3) in a beaker. Dissolve 1.60 g of tantalum (V) ethoxide in 28 ml of anhydrous ethanol. Add the resulting solution dropwise to the beaker through a dropping funnel over 5 minutes at ambient temperature until the precursor is soaked in liquid. No visible liquid film is formed above the precursor p-CAM.3.1. Stir the resulting slurry in a beaker for 30 minutes. Step (b.2.3) is carried out under a nitrogen environment. The individual amounts of Ta and Ni are set to ensure that the molar ratio of Ni:Ta is 0.991:0.003.
[0198] Step (c.2.3): Subsequently, the ethanol was removed by heating the slurry at 120° C. for 6 hours under vacuum to obtain p-CAM.3.2.
[0199] Steps (d.3) and (e.3): The precursor p-CAM.3.2 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Ta+Ga+Mo) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 hours and at 700°C for 6 hours under an oxygen atmosphere (10 exchanges / h) using a heating rate of 3°C / min and a cooling rate of 10°C / min. The material thus obtained was then sieved with a mesh size of 30 μm to obtain CAM.3 of the present invention having a D50 of 6 μm.
[0200] Preparation of the material CAM.4 of the present invention:
[0201] Step (b.1.4) and step (c.1.4): 0.68 g of magnesium nitrate and 3.22 g of ammonium zirconium (IV) carbonate are dissolved in 100 ml of deionized water. The solution is charged into a dropping funnel and added dropwise to 100 g of the precursor p-CAM.1 placed in a beaker at ambient temperature over a period of 5 minutes until the precursor is soaked in liquid, but then a visible liquid film is formed on the precursor p-CAM.1. During this procedure, the precursor p-CAM.1 is stirred in the beaker for 30 minutes. Subsequently, the slurry is heated at 120°C for 6 hours under vacuum to remove the water. In a similar case to that listed above, the remaining magnesium and zirconium solutions are added to the dried pCAM until the precursor is completely soaked in liquid again, but then a visible liquid film is formed. Subsequently, the mixture is heated at 120°C for another 6 hours under vacuum to remove the water. The procedure is repeated until all the zirconium and magnesium solutions are consumed. After final drying at 120° C. for 6 hours, p-CAM.4.1 was obtained. The individual amounts of Mg, Zr and Ni were set to ensure a molar ratio of Ni:Mg of 0.991:0.002 and a molar ratio of Ni:Zr of 0.991:0.004.
[0202] Step (b.2.4): Place p-CAM.4.1 obtained from (c.1.4) in a beaker. Dissolve 1.12 g of titanium (IV) isopropoxide in 28 ml of anhydrous ethanol. Add the resulting solution dropwise to the beaker through a dropping funnel over 5 minutes at ambient temperature until the precursor is soaked in liquid. No visible liquid film is formed above the precursor p-CAM.4.1. Stir the resulting slurry in a beaker for 30 minutes. Step (b.2.4) is carried out entirely under a nitrogen environment. The individual amounts of Ti and Ni are set to ensure that the molar ratio of Ni:Ti is 0.991:0.003.
[0203] Step (c.2.4): Subsequently, the mixture was heated at 120° C. for 6 hours under vacuum to remove the ethanol to obtain the impregnated p-CAM.4.2.
[0204] Steps (d.4) and (e.4): The precursor p-CAM.4.2 was mixed with LiOH·H2O in a molar ratio of Li:(Ni+Mg+Ti+Zr) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 hours and at 700°C for 6 hours under an oxygen atmosphere (10 exchanges / h) at a heating rate of 3°C / min and a cooling rate of 10°C / min. The material thus obtained was subsequently sieved with a mesh size of 30 μm to obtain CAM.4 according to the invention having a D50 of 6 μm.
[0205] Preparation of comparative cathode active material C-CAM.5:
[0206] Step C-(b.1.5): Place 100 g of the precursor p-CAM.1 in a beaker. Dissolve 6.54 g of cobalt (II) nitrate in 35 ml of deionized water. Add the resulting solution dropwise to the beaker through a dropping funnel over 5 minutes at ambient temperature until the precursor is soaked with liquid. No visible liquid film is formed above the precursor. Stir the resulting slurry in a beaker for 30 minutes. Set the individual amounts of Co and Ni to ensure a molar ratio of Ni:Co of 0.98:0.02.
[0207] Step C-(c.1.5): Subsequently, the mixture was heated at 120° C. for 6 hours under vacuum to remove water to obtain comparative precursor p-CAM.5.
[0208] Step C-(d.1.5) and (e.1.5): The comparative precursor Cp-CAM.5 was mixed with LiOH·H2O at a molar ratio of Li:(Ni+Co) of 1.01:1, poured into an alumina crucible and heated at 350°C for 4 hours and at 700°C for 6 hours under an oxygen atmosphere (10 exchanges / h) at a heating rate of 3°C / min and a cooling rate of 10°C / min. The material thus obtained was then sieved with a mesh size of 30 μm to obtain a comparative cathode active material C-CAM.5 having a D50 of 6 μm.
[0209] Electrode preparation: The electrode contained 94% CAM, 3% carbon black (Super C65) and 3% binder (polyvinylidene fluoride, Solef 5130). The slurry was mixed in N-methyl-2-pyrrolidone and cast on aluminum foil with a doctor blade. After the electrode was vacuum dried at 105°C for 6 hours, the circular electrode was punched, weighed and vacuum dried at 120°C for 12 hours and then sent to an argon-filled glove box.
[0210] Half-cell electrochemical measurements: A coin-type electrochemical cell was assembled in an argon-filled glove box. A 14 mm diameter positive electrode (loaded with 8.0 ± 0.5 mg cm -2) were separated from 0.58 thick lithium foil by a glass fiber separator (Whatman GF / D). 1M LiPF6 in a weight ratio of 3:7 ethylene carbonate (EC): ethyl methyl carbonate (EMC) in an amount of 95 μl was used as electrolyte. The cell was galvanostatically cycled between 3.1 and 4.3 V at room temperature on a Maccor 4000 cell resistance cycler by applying the following C-rate until 70% of the initial discharge capacity was reached at a specific discharge step.
[0211] Table 1: Electrochemical test procedures for coin cell half-cells
[0212]
[0213]
[0214] After charging at the listed C-rate, all charging steps except the first were completed by a constant voltage step (CV*) lasting 1 hour, or until the current reached 0.02C.
[0215] During the cycling process, data points were collected every 1 minute or after a voltage change of at least 5 mV occurred. Four electrochemical cells were assembled for each material, and the corresponding cycling curves, capacity, and resistance were obtained by averaging the four cells.
[0216] During the resistance measurement (performed every 25 cycles at 25°C), the cell was charged at 0.2°C to a state of charge of 50% relative to the previous discharge capacity. To balance the cell, an open circuit step of 30 minutes followed. Finally, a discharge current of 2.5°C was applied for 30 seconds to measure the resistance. At the end of the current pulse, the cell was again balanced in open circuit conditions for 30 minutes and further discharged at 0.2C to 3.0 V.
[0217] To calculate the resistance, the voltage V0s before applying the 2.5C pulse current, the voltage V30s 30 seconds after the 2.5C pulse current, and the 2.5C current value (j, A) were measured. The resistance was calculated according to Equation 3 (V: voltage, j: 2.5C pulse current).
[0218] R = (V0s - V30s) / j (Equation 3)
[0219] Table 2: Comparison of the composition and electrochemical properties of cathode active materials C-CAM.1 and C-CAM.5 and cathode active materials CAM.2, CAM.3 and CAM.4 of the present invention
[0220]
[0221]
[0222] nd: not determined
Claims
1. With composition Li 1+x TM 1-x O2 granular material, wherein x is in the range of -0.02 to +0.05, TM is (Ni 1-x1-x2 M 1 x1 M 2 x2 ), where x1>0, x2>0 and x1+x2≤0.07, Among them, M 1 is selected from Nb, Ta, Ti, Zr, W and Mo, Among them, M 2 is selected from B, Al, Mg and Ga, The particulate material has an average particle diameter (D50) in the range of 2 to 20 μm.
2. A particulate material according to claim 1, wherein TM is a metal combination according to formula (I): (Ni a M 1 b M 2 c ) 1-d M 3 d (I) in M 3 Selected from Mn and Co, a is in the range of 0.95 to 0.995, b is in the range of 0.002 to 0.04, c is in the range of 0.002 to 0.02, and d is 0, a+b+c=1.
3. The granular material according to claim 1, wherein M 1 is Zr or Ti and M 2 For Al.
4. The granular material according to claim 2, wherein M 1 is Zr or Ti and M 2 For Al.
5. The granular material according to claim 1, wherein M 1 is Ta or Nb and M 2 It is Al or B.
6. The granular material according to claim 2, wherein M 1 is Ta or Nb and M 2 It is Al or B.
7. A granular material according to any one of claims 1 to 6, wherein the material has an integrated peak width (2nd charge IPW) in the differential capacity plot (dQ) / (dV) between 4.1 and 4.25 V in the second charge cycle at 0.2C rate of at least 25 mV 4.1-4.25V .
8. A particulate material according to any one of claims 1 to 6, wherein the material is coated with a metal oxide.
9. A particulate material according to claim 7, wherein the material is coated with a metal oxide.
10. A particulate material according to any one of claims 1 to 6, wherein b ≤ c.
11. The granular material according to claim 7, wherein b ≤ c.
12. The granular material according to claim 8, wherein b ≤ c.
13. The granular material according to claim 9, wherein b ≤ c.
14. A method for preparing a granular material according to any one of claims 1 to 13, wherein the method comprises the following steps: (a) providing particulate nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide, (b) Use one or two M 1 and M 2 treating the particles with a solution of a compound of nickel hydroxide, nickel (II) oxide or nickel oxyhydroxide, (c) optionally, removing the solvent from step (b), (d) adding a lithium source, (e) heat treating the mixture obtained in step (d).
15. The method according to claim 14, wherein step (e) is carried out at a maximum temperature in the range of 650 to 750°C.
16. The method according to claim 14 or 15, wherein step (c) is performed by a solid-liquid separation method.
Citation Information
Patent Citations
Tantalum doped nickel cobalt aluminium lithium ion battery cathode material
CN107732179A
Niobium-doped lithium nickel-cobalt-aluminum ion battery cathode material
CN107742717A
High-nickel and low-cobalt ternary cathode material and preparation method thereof
CN108767239A